Maternity care providers' perspectives on late-term gestation management (LATE-study): A cross-sectional survey. - Anna E Seijmonsbergen-Schermers; Fatima Hammiche; Hannah de Klerk; Judit K J Keulen; Caroline J Bax; Lilian L Peters; Corine J Verhoeven (PLoS ONE)
Objective To examine the experiences, perspectives, and impact on daily work of maternity care providers regarding the updated Dutch national guideline on the management of late-term pregnancies. Design and setting This was a cross-sectional survey for maternity care providers in the Netherlands in 2024. Methods An online questionnaire was developed, improved on the basis of four semi-structured interviews, piloted, and distributed to primary care and hospital-based midwives, residents, and obstetricians. A 5-point Likert Scale was used for most questions. Descriptive analyses and data visualisation were performed. Linear regressions were performed to assess the association between characteristics and agreement with and adherence to the recommendations. The main outcome measures were awareness of the guideline, agreement with and adherence to the recommendations, opinions and perspectives on the impact of the guideline, and experiences of participants regarding the guideline. Results A total of 643 care providers were included, of whom 53% were primary care midwives, 29% obstetricians/residents and 19% hospital-based midwives. There was 72% agreement and 87% adherence to "offer induction of labour (IOL) at 41 weeks alongside expectant management". Although 92% agreed with "discuss the advantages and disadvantages", only 67% agreed with "specify perinatal outcomes" and 63% agreed with "specify outcomes for nulliparous versus multiparous women". Adherence to these and to recommendations regarding monitoring were lower (43-59%). There was uncertainty among 45% about the benefits of the guideline, with only 17% believing in maternal and 20% believing in neonatal benefits. Conclusions Care providers widely agreed with and adhered to the recommendation to offer IOL at 41 weeks, but adherence to specific elements of shared decision-making was lower, and care providers expressed limited confidence on the benefits of the policy for mother and child.